Correlation Between IL-10 and microRNA-187 Expression in Epileptic Rat Hippocampus and Patients with Temporal Lobe Epilepsy - Alsharafi, Walid A.; Xiao, Bo; Abuhamed, Mutasem M.; Bi, Fang-Fang; Luo, Zhao-Hui (Frontiers in Cellular Neuroscience, 2015)
Accumulating evidence is emerging that microRNAs (miRs) are key regulators controlling neuroinflammatory processes, which are known to play a potential role in the pathogenesis of temporal lobe epilepsy (TLE). The aim of the present study was to investigate the dynamic expression pattern of interleukin (IL)–10 as an anti-inflammatory cytokine and miR-187 and post-transcriptional inflammation-related miRNA in the hippocampus of a rat model of status epilepticus (SE) and patients with TLE. We performed a real-time quantitative PCR and western blot on rat hippocampus (2 hours, 7 days, 21 days and 60 days) following pilocarpine-induced SE, and on hippocampus obtained from TLE patients and normal controls. To detect the relationship between IL-10 and miR-187 on neurons, lipopolysaccharide (LPS) and IL-10-stimulated neurons were prepared. Furthermore, we identified the effect of antagonizing of miR-187 by its antagomir on IL-10 secretion. Here we reported that that IL-10 secretion and miR-187 expression levels are inversely correlated after SE.. In patients with TLE, the expression levels of IL-10 was also significantly upregulated, whereas miR-187 expression was significantly downregulated. Moreover, miR-187 expression was significantly reduced following IL-10 stimulation in an IL-10–dependent manner. On the other hand, antagonizing miR-187 reduced the production of IL-10 in hippocampal tissues of rat model of SE. Our findings demonstrate a critical role of miR-187 in the physiological regulation of IL-10 anti-inflammatory responses and elucidate the role of neuro-inflammation in the pathogenesis of TLE. Therefore, modulation of the IL-10 / miR-187 axis may be a new therapeutic approach for TLE.